Web Services Integration Strategy with Minimum Hops Constraint in Wireless Sensor Networks. (6th February 2014) - Ouyang, Wen; Chen, Min-Lang
Both wireless sensor networks and service-oriented architectures (SOA) are very popular distributed computing paradigm. Web service is a widely accepted implementation of SOA. However, web service is based on Internet protocols and requires adaptation to suit the restrictions posed by WSNs. The development of Internet of Things has triggered research of web services of WSNs which made the consolidation of these technologies possible. At the same time, web service integration enables the support of more functionalities since many applications rely on not just one web service, but a whole school of them. Thus, how to compose and integrate different web services efficiently to provide complicated services becomes an essential topic. This paper investigates a problem which minimizes the number of hops of web services while integrating these web services to finish a set of tasks. We call this problem Minimum Hops of Service Integration Problem. It is proved that, when there are no precedence relationships between the tasks, the decision problem is NP-complete. This implies that this web services integration problem is NP-hard. For the case when the relationships between the tasks are in linear order, a polynomial-time, optimal web service integration algorithm, using greedy strategy, is provided.